Past and Present: A Review of Antenatal Corticosteroids and Recommendations for Late Preterm Birth Steroids - Dixon, C. Luke; Too, Gloria; Saade, George R.; Gyamfi-Bannerman, Cynthia (American Journal of Perinatology, 2018)
Since 1972, the beneficial neonatal effects of antenatal corticosteroids (ACSs) have been repeatedly demonstrated in pregnancies at risk of preterm birth before 34 weeks' gestation. While ACS utilization before 34 weeks has been high since the 1990s, knowledge gaps regarding the risks and benefits of ACS continue to exist. Recent evidence has been published regarding the benefit of ACS in the late preterm period. This review addresses the evidence and knowledge gaps for ACS use before and after 34 weeks' gestation. We also provide recommendations for ACS use in the late preterm period.
Keywords: antenatal corticosteroids; betamethasone; dexamethasone; fetal; maturity; late preterm steroids